Change-in-support reactions for balance recovery. - Maki, B.E (IEEE Engineering in medicine and biology magazine)
The authors provide an overview of their own recent research in "change-in-support" reactions covering control mechanisms, age-related changes, and implications for fall prevention. Compensatory stepping and grasping are critical reactions for preventing falls. These reactions are much more rapid than volitional limb movements and can be very effective in decelerating the center of mass (COM) motion induced by sudden unpredictable perturbation, despite environmental constraints on limb trajectory and additional demands imposed by ongoing physical or cognitive activity. However, even healthy older adults experience difficulty in controlling these reactions, and they appear to have particular problems in controlling lateral stability and lateral leg movement. These problems may be particularly relevant to the problem of hip fractures, which are most likely to occur as a result of a lateral fall. Older adults also appear to be more reliant on grasping reactions than young adults, but they are less able to execute these reactions rapidly. From a clinical perspective, it is important to assess compensatory stepping and grasping. Such tests could be used as a screening tool to identify high-risk individuals and could also serve to pinpoint specific control problems to target for balance training or other intervention. More effective use of stepping and grasping reactions can be promoted through improved design of footwear, mobility aids, handrails, and grab-bars.